THINKING UI/UX DESIGN ONLINE DESCOVERY EVENT TICKETS - Ihsan, Mohammad Maftuh; Hananto, April Lia; Tukino; Huda, Baenil (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
This research discusses designing the UI/UX appearance of an online ticket-purchasing application called Discovery Event to solve problems such as the absence of a group chat feature, late withdrawals of funds, and location points in the application. In implementing UI/UX Design Thinking in online ticket purchasing applications, several stages must be carried out: Empathize, Define, Ideate, Prototype, and Test. The Design Thinking method is used to create solutions to solve problems felt by users. The research results show that Discovery Event can solve problems by improving the group chat feature, efficient fund withdrawals, and adding location point features. Tests involved 20 respondents, which showed user satisfaction with the application interface design. Discovery Event offers an attractive and user-friendly interface and provides a foundation for better application development in the future. Keywords: Online ticket purchasing, Discovery Event, Design Thinking, UI, UX.